Hydrodynamic focusing in microchannels under consideration of diffusive dispersion : theories and experiments - Wu, Zhigang (2014)
This paper investigates hydrodynamic focusing inside a microchannel. Hydrodynamic focusing has a number of applications in microfluidics such as micromixer, microcytometer, fluidic switch, and cell infection. In contrast to most of the previous works, hydrodynamic focusing phenomenon in this study is described analytically with a two-phase Navier–Stokes equation system. The model considers the effect of the different viscosities of the sample stream and the sheath streams. Based on this theory, the width of the sample flow cannot only be adjusted by the flow rates but also by the viscosity ratio between the sheath stream and the sample stream. Furthermore, the effect of diffusive dispersion between the sheath stream and the sample stream is investigated analytically and numerically. This effect is important for applications such as mixing and cell infection. The velocity field and concentration field of hydrodynamic focusing was measured using fluorescent techniques. Micro particle image velocimetry (micro-PIV) was used for measuring the velocity of the three streams quantitatively, while the concentration field was evaluated from fluorescent images. The results presented in the paper are fundamental for the design of hydrodynamic focusing in microfluidics.